Assessing methods to improve benthic fish sampling in a stony headwater stream. Issue 4 (19th November 2021) - Pritchard, Eleri G.; Chadwick, Daniel D. A.; Chadwick, Michael A.; Bradley, Paul; Sayer, Carl D.; Axmacher, Jan C.
Abstract: Electrofishing is a well‐established and widely used method for surveying fish populations. Nonetheless, its effectiveness is impacted by numerous factors, including water chemistry, habitat type and fish species. Both physiological and behavioural responses make bottom‐dwelling 'benthic' fish which lack swim bladders (e.g. European bullhead Cottus gobio ) particularly difficult to survey by electrofishing. We compare the performance and practicalities of electrofishing for benthic fish at a rocky northern English headwater stream with two sampling methods originally designed for crayfish surveys; the triple drawdown method which involves repeated dewatering of a site, and the Pritchard Trap method which involves sunken traps filled with natural substrate that samples a small, fixed (0.25 m 2 ) area of river bed. Both the Pritchard trapping and triple drawdown methods provided similar high‐density population density estimates for bullhead which were at least 2.5–5 times higher than predicted from electrofishing derived sweep depletion curves. Electrofishing and the triple drawdown method are both resource‐intensive, requiring expensive equipment and a team of trained operatives. These approaches also pose a risk to fish and non‐target organisms. In contrast, Pritchard Traps provide a cost‐effective passive, low risk survey method requiring minimal training and only one operative. Pritchard traps, therefore, show particular promise for benthic fish surveying and monitoring. Abstract : The 'Pritchard Trap' (PT, left) presents a novel method to survey benthic fish. The method was tested in a rocky headwater in Northern England and was compared to the Triple Drawdown (TDD) technique and electrofishing. Whilst electrofishing severely underestimated the density of European bullhead (Cottus gobio [italics] right), the PT and TDD methods both generated robust quantitative population data including density and size structure. The PT presents a cost‐effective approach to benthic fish sampling, wih relatively low sampling effort.